2015
DOI: 10.1186/s12909-015-0390-6
|View full text |Cite
|
Sign up to set email alerts
|

Puzzle-based versus traditional lecture: comparing the effects of pedagogy on academic performance in an undergraduate human anatomy and physiology II lab

Abstract: BackgroundA traditional lecture-based pedagogy conveys information and content while lacking sufficient development of critical thinking skills and problem solving. A puzzle-based pedagogy creates a broader contextual framework, and fosters critical thinking as well as logical reasoning skills that can then be used to improve a student’s performance on content specific assessments. This paper describes a pedagogical comparison of traditional lecture-based teaching and puzzle-based teaching in a Human Anatomy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 15 publications
(15 reference statements)
4
24
1
Order By: Relevance
“…Finding the ideal form to provide students with sustainable knowledge is the subject of several different studies. Although there are many studies comparing two or more instruction forms [24], there are no studies that compare traditional teaching methods to self-directed learning within the course of a modern medical curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Finding the ideal form to provide students with sustainable knowledge is the subject of several different studies. Although there are many studies comparing two or more instruction forms [24], there are no studies that compare traditional teaching methods to self-directed learning within the course of a modern medical curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…This is also supported by other studies for different validity levels [ 18 , 23 ]. As these assessments are often focused on a specific part of procedural knowledge [ 24 ], we also measured knowledge gain in terms of declarative knowledge. The comparison of pre- and posttest performance revealed an increase in declarative knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Inside this box were educational puzzle games, quizzes created a unique, thus stimulating the activity of the child, so that the educational material can be easily remembered and applied by children. 7 Pratiwi et al 8 conducted a study on the influence of educational game methods and lecture methods on knowledge, attitudes, and actions about diarrheal disease in elementary school children in Kendari and found that educative game methods were more effective in changing knowledge, attitudes, and actions. This was because the accuracy of the election of the extension methods used in the experimental group matched the characteristics of respondents, i.e.…”
Section: Discussionmentioning
confidence: 99%